ANALISIS EKONOMI USAHA SAPI POTONG DI LAHAN PERKEBUNAN SAWIT DAN KARET - S. Rusdiana; R. Hutasoit; J. Sirait (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
The  study  was  conducted  in  the  village  of  Pulo  Bandring  Tanah  Rakyat District of Asahan in North Sumatra Province. The study was conducted in 2015 using the method of field survey on 30 respondent beef cattle farmers in a way purposive random sampling. The primary data obtained through interviews directly in the field with farmers beef cattle, which refers to the questionnaire has been prepared, while secondary  data  obtained  from  the  Extension  Service,  Plantation,  Agriculture  and Livestock  local,  then  the  data  collected  was  processed  and  tabulated  descriptive, quantitative  and  economic  analysis.  The  purpose  of  this  paper  is  to  determine  the economic analysis in the beef cattle business in a manner shepherd breeder dilahan palm and rubber plantations in Asahan. The results showed that the net income of the business of cattle by means of grazing dilahan oil palm and rubber plantations around Rp.3.185.000/breeder/year with B/C ratio of 1.2. Labor  breeder  beef cattle by about 20,000  working time/day 8 hours is calculated based on the first working Hok / day. For the breeders of beef cattle in the Village People's District of Pulobandring Asahan immediately in the push towards commercial business, so that the cattle were reared by farmers to grow, can produce well, and pertamabahan body weight increases, so that the sale value of cattle higher in terms of the market price of cattle.